2005
DOI: 10.1634/theoncologist.10-90001-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Ibandronate in Metastatic Bone Disease: Review of Clinical Data

Richard Bell

Abstract: Bone involvement is a significant complication of metastatic cancer that occurs in up to 95% of multiple myeloma patients, up to 75% of breast and prostate cancer patients, and 15%-40% of patients with primary lung, colon, or kidney tumors [1,2]. Bone metastases cause considerable morbidity, including severe pain, immobility and disability, pathologic fractures, life-threatening hypercalcemia, and spinal cord compression. These problems have a major impact on patient quality of life. The spread of tumor cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…Many reviews have reported that ibandronate is able to reduce bone pain, to improve significantly global QoL and physical functioning, with an acceptable toxicity profile 5,[19][20][21][22][23] . Oral ibandronate is cost-effective for the management of bone metastases from breast cancer, providing effective reduction of skeletal-related events and avoiding resource use and costs associated with bisphosphonate infusion [24][25][26] .…”
Section: Discussionmentioning
confidence: 99%
“…Many reviews have reported that ibandronate is able to reduce bone pain, to improve significantly global QoL and physical functioning, with an acceptable toxicity profile 5,[19][20][21][22][23] . Oral ibandronate is cost-effective for the management of bone metastases from breast cancer, providing effective reduction of skeletal-related events and avoiding resource use and costs associated with bisphosphonate infusion [24][25][26] .…”
Section: Discussionmentioning
confidence: 99%
“…The goals of treatment for bone metastases are also to prevent disease-related skeletal complications, palliate pain, and maintain quality of life. Zoledronate, 104 pamidronate, clodronate, and ibandronate 105,106 have demonstrated efficacy compared with placebo.…”
Section: Clinical Applications Of Bisphosphonatesmentioning
confidence: 99%
“…Several factors may explain these differences (Table 1). Clinical evidence for differences is discussed elsewhere [35].…”
Section: Rationale For Renal Safety Differencesmentioning
confidence: 99%
“…This difference may indicate that ibandronate has a broader renal safety margin and is less likely to cause renal damage Table 1. Preclinical data on bisphosphonates suggest that renal safety profiles differ [15,35] Abbreviation: LOEL, lowest observed effect level.…”
Section: Rationale For Renal Safety Differencesmentioning
confidence: 99%